2011
DOI: 10.1128/jcm.01822-10
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence and Predominance of Hepatitis Delta Virus Genotype 1 Infection in Cameroon

Abstract: Antibodies to the hepatitis delta virus (HDV) were found in 17.6% of 233 hepatitis B virus surface antigenpositive subjects in Cameroon. Phylogenetic analyses showed the presence of HDV-1, HDV-5, HDV-6, and HDV-7 genotypes. These results enrich the limited data on HDV prevalence and molecular diversity in Cameroon.Hepatitis delta virus (HDV) is associated with hepatitis B virus (HBV) infection and is frequently related to more severe disease than that due to the underlying HBV monoinfection (5, 10). HDV infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 12 publications
4
40
2
Order By: Relevance
“…The rare HDV seroprevalence studies that have been performed during the past 15 years and the recent reports of the African clades 5 to 8 (5,6) als), Gabon (15.6% to 70.6%), Mauritania (14.7% to 33.1%), Mozambique (0%), Nigeria (0% to 12.5%), and Senegal (3.2%), revealed various HDV antibody rates (2,(15)(16)(17)(18)(19)(36)(37)(38)(39)(40). Interestingly, also in our study, the HDV Ab prevalences varied widely and ranged from 0% to 27.3% in asymptomatic carriers and from 1.3% to 50% in liver patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rare HDV seroprevalence studies that have been performed during the past 15 years and the recent reports of the African clades 5 to 8 (5,6) als), Gabon (15.6% to 70.6%), Mauritania (14.7% to 33.1%), Mozambique (0%), Nigeria (0% to 12.5%), and Senegal (3.2%), revealed various HDV antibody rates (2,(15)(16)(17)(18)(19)(36)(37)(38)(39)(40). Interestingly, also in our study, the HDV Ab prevalences varied widely and ranged from 0% to 27.3% in asymptomatic carriers and from 1.3% to 50% in liver patients.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 15 were attributed to these supposedly "African" clades, while 10 strains clustered with clade 1 (5,6). Despite their characterization as African clades, only few genotyping studies have been performed in Africa (Cameroon, clades 1, 5, 6, 7; Gabon, clades 1, 7, and 8; Mauritania, clades 1 and 5), and clade 1 dominated in all cohorts (2,5,6,(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2009, an antibody rate of 66.7% was reported in Gabon (Makuwa et al 2009). In Cameroon (Foupouapouognigni et al 2011), anti-HD was found in 17.6% of 233 patients with CHB at two medical centers. In Nigeria, anti-HD was found in 12.5% of 96 patients with HBsAg liver disease (Nwokediuko and Ijeoma 2009), and in Mauritania, in 14.7% of HBsAg-positive pregnant women (Mansour et al 2012).…”
Section: Epidemiological Changes In the Last Two Decades In Europementioning
confidence: 99%
“…Interestingly, these results showed that HCV infection may lead to slower emergence of P. falciparum in blood [137]. Other studies have demonstrated the usefulness of the PCR as a tool for the description of the molecular diversity of other less known/marginal viruses in this region, such as hepatitis delta virus in Cameroon [139] and in Gabon [140], or hepatitis GB-C/HG virus and TT virus in Gabon [141].…”
Section: Hepatitis Virusesmentioning
confidence: 99%